If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4z + 5) = -3z + -60 Reorder the terms: 3(5 + 4z) = -3z + -60 (5 * 3 + 4z * 3) = -3z + -60 (15 + 12z) = -3z + -60 Reorder the terms: 15 + 12z = -60 + -3z Solving 15 + 12z = -60 + -3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3z' to each side of the equation. 15 + 12z + 3z = -60 + -3z + 3z Combine like terms: 12z + 3z = 15z 15 + 15z = -60 + -3z + 3z Combine like terms: -3z + 3z = 0 15 + 15z = -60 + 0 15 + 15z = -60 Add '-15' to each side of the equation. 15 + -15 + 15z = -60 + -15 Combine like terms: 15 + -15 = 0 0 + 15z = -60 + -15 15z = -60 + -15 Combine like terms: -60 + -15 = -75 15z = -75 Divide each side by '15'. z = -5 Simplifying z = -5
| -3y+9=-4y+2 | | 72-4n=-22 | | -2v^2-v+12=-3v^2+6w | | 2(x-2)=16x^2-5x | | 12x-8=36x+10 | | 9n-2=7n+5 | | x-3=2x+2 | | 3x-(2x+4)=4x-49 | | 8x+5x-63=42-8x | | 3(x-2)+3-2x=1 | | 5x+8=3+7x-7 | | -3+5= | | 7x-(4x+3)=15 | | -4-(2x-2)=-8(x+4) | | 2+0.5g+9=16 | | 5.50=3+0.25x | | 5x+45=x^2-5 | | 7y=-10 | | 5x+16=6x+11 | | -6x+9+7x=6+x+3 | | .5x+2y=235 | | 5.50=3+0.25 | | -9n=12n-45 | | 6m+6m=40+20-12 | | 4x=-16x+3 | | x-3=x+6 | | 14+25m=28+18m | | 5.50=3+0.8x | | 3.10x-2.5=2 | | -(7y+3)-(-6y-6)=-1 | | 7x+9y-9(7x-6y+3z)= | | y=35x+70 |